Impact of organic and integrated production systems on yield and seed quality of rainfed crops and on soil properties - Gopinath, Kodigal A.; Venkatesh, Govindarajan; Manjunath, Mallappa; Jayalakshmi, Mitnala; Prasad, Telaprolu Venkata; Rajkumar, Bollam; Venugopalan, Visha Kumari; Raju, Bellapukonda Murali Krishna; Prabhakar, Mathyam; Chary, Gajjala Ravindra; Singh, Vinod Kumar (Frontiers in Nutrition, 2023)
Organic farming is the most talked about sector in agricultural production. However, sufficient scientific information on several aspects of organic farming based on long-term studies is lacking particularly under rainfed conditions of India. The purpose of this study was to assess the long-term impact of organic and integrated production systems on crops yield and quality, economic returns and soil properties. The study was conducted with three crops, sunflower (Helianthus annuus L.), pigeonpea (Cajanus cajan L.) and greengram [Vigna radiata (L) Wilczek] under three different production systems, control (use of chemical inputs alone), organic and integrated. We found that the average production of integrated system is was on par with organic management and recorded significantly higher pigeonpea equivalent yield (PEY) (827 kg ha-1) compared to control (chemical inputs) (748 kg ha-1). The yield gap between organic and integrated production systems declined from fourth year for greengram and eighth year for sunflower, during the 10-year experimental period whereas the pigeonpea yield was similar under both production systems from first yearthe yield gap for all three crops between organic and conventional production systems declined during a 10-year experimental period. Plots under organic management had significantly lower bulk density (1.18 Mg M-3), higher water holding capacity (38.72%) and porosity (53.79%) compared to integrated production system and control (chemical inputs). The soil organic C (SOC) content under organic production system was 32.6% more than the initial organic carbon of the soil (0.43%), with higher soil N (205.2 kg ha-1). Plots under integrated production system, however, had higher soil N (205.2 kg ha-1) and P (26.5 kg ha-1) compared with other treatments. The dehydrogenase activity (5.86 µg TPF g-1 soil h-1) and microbial biomass carbon (317.3 µg g-1 soil) content was higher in the plots under organic production system than under other systems. Organically produced pigeonpea and greengram seeds had marginally lowersimilar protein content with that of integrated system, and higher K and micronutrient (Fe, Zn, Cu and Mn) contents than other treatments. The results show the potential of organic production system in improving crop yields, soil properties and produce quality in semiarid rainfed areas.